Impact of Danish Livestock and Manure Management Regulations on Nitrogen Pollution, Crop Production, and Economy - Sommer, Sven G.; Knudsen, Leif (Frontiers in Sustainability, 2021)
Reduction of nitrate (NO3) and ammonia (NH3) emission to the environment has, since the 1980s, been targeted by Danish environmentally friendly regulations. Nitrate pollution of aquifers and surface waters caused by farming was observed at the start of the 1980s, and in the mid-1980s, NH3 emission was known to contribute reactive nitrogen (N) to the environment. Manure is a significant source of plant nutrient loss, because there might be a lack of economic incentives and knowledge for the farmers to obtain a high nutrient utilization of the manure. This article gives a presentation of the initiatives and regulations intended to reduce the emission, the actual reduction in emission achieved, and the effect of the regulation on farmers' economy, which is considered important in the discussion about how we can reduce pollution of the environment and at the same time have an economically sustainable agriculture. In the 1980s, the Ministry of Environment and the farmers' union agreed on launching a “good agricultural practice” program, aimed at reducing N loss by increasing N use efficiency and reducing fertilizer N import. This had no or limited effect on emission, and in the late 1980s, regulations were introduced with mandatory stipulations on manure storage capacity, application of manure during the growing season, and limitation on the number of animals per hectare agricultural land (Harmony Rules). Early introduction of the Harmony Rule in 1985 has since prevented very high local surpluses of N and phosphorus. In 1993/94, legislation was introduced for a system of farm-specific N quotas and minimum requirements for utilization of N in animal manure, controlled by the Ministry of Agriculture and Environment based on fertilizer accounts for each farm. The legislation requirements for utilization of N in manure were based on research at the universities and a large number of trials on commercial farms conducted by the Danish extension service (SEGES). These convinced most farmers of the potential manure N fertilizer efficiency. From 1993/94, the N quotas were based on optimal N levels to the crops, but from 1998/99 to 2016/17, they were reduced to 10–20% below the economically optimal rate. From 2016/17, the reduced N quotas were replaced by an expansion of the catch crop requirement in the legislation. The effect is that NO3- leaching has been reduced by 45% by restricting manure application to the period with crop demand for plant nutrients, by undersupplying with N as related to the economically optimum application rate, and by compulsory cultivation of crops that take up N during most of the year. Regulation has resulted in a 51% reduction in NH3 emission from livestock buildings, manure stores, and manure application. In 2020/21, the required N fertilizer efficiency of manure N (equivalence to N in mineral fertilizers) is 75% of N in cattle slurry and 80% for pig slurry, higher than in any other countries known to us. The N quotas are based on the optimal level, and the requirement for compulsory catch crops is 40–50% for the main part of the country. The farmers can use alternatives to catch crops like a reduced N quota or early establishment of winter cereals. The revision of the “regulation system” was intended to improve the economy of the crop production, but the effect was that complexity and volume of legislation have increased significantly, without much effect on farmers' economy. It is recommended that the regulation is kept simple and that it reflects the processes leading to plant uptake and emissions.